Analisis Kepuasan Konsumen pada JNE Cabang Palembang - Henti Purnamasari; Efrina Masdaini; Eni Cahyani (Politeknik Negeri Sriwijaya, 2021)
The purpose of this study was to determine the quality of service delivery of goods on customer satisfaction at JNE Palembang Branch. The population of this study are consumers who use the JNE Palembang branch service delivery service. During the COVID-19 pandemic, researchers did not conduct face-to-face interviews. Data collection techniques with snowball sampling using Google Form. In the first stage, the researcher gave permission to the JNE Manager, so that JNE would know that research would be carried out related to their services. The second stage is distributing the questionnaire URL through Whattapps. The questionnaire was collected as many as 100 people. The author uses descriptive statistical analysis techniques, the data is analyzed using the community satisfaction index (IKM). There are 10 indicators studied. Each service has the same weight. The results show that the service elements in the index are at the service interval very satisfied on each indicator of the ease of service procedures, the conformity of service requirements with the type of service, the discipline of service personnel, the responsibility of service officers, the ability of service officers, the speed of service, the politeness and friendliness of the officers, the suitability of the costs paid at a specified fee, the accuracy of the implementation of the service time schedule, comfort in the service unit environment. Practical implications for JNE Palembang Branch, the results of research in the form of information can be used to further improve the quality of service providers from these factors so as to achieve the goals and vision of JNE.